Study on Cavitating Flow Inside Orifice and Spray Angle Near Nozzle Tip According to the Position of Needle Using Enlarged Transparent Acrylic Nozzle - Kim, Byunggyun; Ro, Seungcheon; Park, Suhan; Kim, Young-Bae; Choi, Byungchul; Jung, Seunghun; Lee, Dong-Weon (International journal of automotive technology, 2021)
This study aims to analyze effect of needle position inside nozzle on the internal and external flow characteristics. To visualize cavitating flow inside nozzle, the transparent acrylic nozzle was used. We tested five needle positions that simulated the needle movement of injector. The cross-section of test nozzle is rectangular with a very narrow width instead of circular shaped for a better visualization of cavitating flow. The inside of the nozzle was visualized by the shadowgraphic visualization using a high-speed camera and a metal-halide lamp. From the experiments, development of the cavitating flow according to the needle positions depends on the flow velocity and the cavitation number. The cavitation length, cavitation width, and spray angle are relatively symmetrically shown when the needle was at the center. However, they were asymmetrical when the needle position was biased. When the needle positions were in the same on the vertical line, the minimum cavitation length, minimum cavitation width, and minimum spray angle were larger when the upper level. The needle position affects the development timing and cavitation growth. When the needle position was located at the upper level, the hydraulic flip occurred at a higher injection pressure than the lower level.